Opinion dynamics meet agent-based climate economics: An integrated analysis of carbon taxation - Teresa Lackner; Luca E. Fierro; Patrick Mellacher (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
The paper introduces an integrated approach, blending Opinion Dynamics with a Macroeconomic Agent-Based Model (OD-MABM). It aims to explore the co-evolution of climate change mitigation policy and public support. The OD-MABM links a novel opinion dynamics model that is calibrated for European countries using panel survey data to the Dystopian Schumpeter meeting Keynes model (DSK). Opinion dynamics regarding stringent climate policy arise from complex interactions among social, political, economic and climate systems where a household's opinion is affected by individual economic conditions, perception of climate change, industry-led (mis-)information and social influence. We examine 133 policy pathways in the EU, integrating various carbon tax schemes and revenue recycling mechanisms. Our findings reveal that while effective carbon tax policies initially lead to a decline in public support due to substantial macroeconomic transition costs, they concurrently drive a positive social tipping point in the future. This shift stems from the evolving economic and political influence associated with the fossil fuel-based industry, gradually diminishing as the transition unfolds. Second, hybrid revenue recycling strategies that combine green subsidies with climate dividends successfully address this intertemporal trade-off, broadening public support right from the introduction of the carbon tax.
Keywords: C63; H31; Q43; Q50; 330; Climate change; mitigation policy; opinion dynamics; agent-based models; transition risks